Determinación de metabolitos primarios, actividades enzimáticas y características físico-químicas de lúcuma (Pouteria lucuma) en dos estados fisiológicos - Janampa Huaytalla, Carmen Saby (2017)
The aim of this study was to determine the physicochemical characteristics, enzymatic activities and primary metabolites in two physiological stages of lucuma. Fruits were harvested in the physiological stages known as inmature (IM) and physiological maturity (PM) from the same tree, four different trees were chosen for sampling. The results related to physicochemical characteristics show that the content of dry matter, soluble solids, soluble fiber, starch and the yellow tone of skin and pulp are lower in IM than in PM stage. Whereas the opposite occurs with the titratable acidity, soluble fiber and pectin contents which are higher in IM stage. Regarding primary metabolites, glucose, myo-inositol, quinic, succinic, palmitic, stearic, oleic and linoleic acids are present in higher ammounts in IM stage while L-ascorbic acid content is higher in PM stage. Polygalacturonase activity was the only enzymatic activity detected and it does not vary among the physiological stages studied. Lastly, characteristics like fatty acids profile, soluble fiber, starch, L-ascorbic acid and myo-inositol contents in PM stage are the main contributors to the final features of this fruit.